2016
DOI: 10.3390/nu9010001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Vitamin B12 Concentrations Are Independent Predictors of In-Hospital Mortality in Adult Patients at Nutritional Risk

Abstract: Background: Elevated plasma vitamin B12 concentrations were identified as predictors of mortality in patients with oncologic, hepatic and renal diseases, and in elderly and critically ill medical patients. The association between vitamin B12 concentrations and in-hospital mortality in adult patients at nutritional risk has not been assessed. Methods: In this five-year prospective study, we investigated whether high vitamin B12 concentrations (>1000 pg/mL) are associated with in-hospital mortality in 1373 not-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
(64 reference statements)
0
20
2
3
Order By: Relevance
“…1 While the deleterious effects of vitamin B 12 deficiency, such as anemia, neuropsychiatric symptoms, and other clinical manifestations, are well established, 2 the potential association of high plasma concentrations of vitamin B 12 with adverse health outcomes has not been fully explored. 3 Indeed, a potential association of high vitamin B 12 plasma concentrations with excess mortality has been assessed in elderly [3][4][5][6][7][8][9] and hospitalized 10,11 populations, but it has not been explored in the general population, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…1 While the deleterious effects of vitamin B 12 deficiency, such as anemia, neuropsychiatric symptoms, and other clinical manifestations, are well established, 2 the potential association of high plasma concentrations of vitamin B 12 with adverse health outcomes has not been fully explored. 3 Indeed, a potential association of high vitamin B 12 plasma concentrations with excess mortality has been assessed in elderly [3][4][5][6][7][8][9] and hospitalized 10,11 populations, but it has not been explored in the general population, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Capello et al . (2017) showed that elevated plasma vitamin B 12 concentrations (>1000 pg mL −1 ) had a significant association (>1000 pg mL −1 ) with mortality in hospitalised patients The risk of the in‐hospital mortality was 2.20 (range 1.56–3.08; P < 0.001), independent of age, gender and body mass index . Hemmersbach‐Miller et al .…”
Section: Discussionmentioning
confidence: 97%
“…Although we did not find data in the literature relating high levels of vitamin B 12 with cognitive damage, a high level of vitamin B associated with damage to health has been found. Capello et al (2017) showed that elevated plasma vitamin B 12 concentrations (>1000 pg mL À1 ) had a significant association (>1000 pg mL À1 ) with mortality in hospitalised patients The risk of the in-hospital mortality was 2.20 (range 1.56-3.08; P < 0.001), independent of age, gender and body mass index (39) . Hemmersbach- Miller et al (2005) reported the available vitamin B 12 levels for 366 patients: 187 nonagenarians and 179 controls aged 65-75 years.…”
Section: Evaluated the Relationship Betweenmentioning
confidence: 99%
“…The group 'High-B12' included all the patients with a B12 ≥ 1000 ng/L. The threshold of 1000 ng/L corresponds to the normal upper limit of our assay, as in previous studies [4,[21][22][23]. The group 'Normal-B12' included patients who had B12 < 1000 ng/L and matched with patients of the High-B12 group according to sex, age, and the hospitalization department, at a 1:1 ratio.…”
Section: Study Populationmentioning
confidence: 99%
“…Although its assay is mainly intended to detect deficiencies, incidental findings of elevated B12 levels are not uncommon [2]. In the absence of a consensus on the threshold that defines an abnormal increased B12 level, elevated B12 is generally defined as a level higher than the upper limit of the reference range, i.e., around 1000 +/− 100 ng/L (738 +/− 73.8 pmol/L) [2][3][4]. Abnormally elevated B12 has been attributed many causes [5,6], e.g., myeloid blood malignancies [7][8][9], acute or chronic liver diseases [10][11][12], chronic kidney failure, autoimmune or inflammatory diseases [3], and Gaucher disease [13].…”
Section: Introductionmentioning
confidence: 99%